Avaliação estrutural da fauna de vertebrados terrestres em área de restauração por transposição de galharia em ambiente de cerrado - Santos, Danilo da Costa [UNESP] (2017)
The development of the human species has brought about significant change in several types of ecosystems. Among the highly degraded Brazilian areas the Cerrado stands out, one of the hotspots with the smallest preservation area in the world. This work aimed to inventory the terrestrial vertebrate fauna pioneer in an area of ecological restoration by brushwood transposition. The study was carried out in the city of Bauru, São Paulo, Brazil, in a degraded area of Cerrado (Cerradão) in the process of ecological restoration and two environment control areas. (one with no disturbance indicators - Cerrado and degraded area –Braquiaria). The methods used for the fauna inventory were pitfall traps, occasional views, identifying vocalizations, and foot traps. Collections occurred between April 2014 and April 2016 summing up 24 months of sampling. A total of 37 species were sampled, with brushwood being the richest environment with 17 species; Braquiaria presented lower richness, with 15 species; and Cerrado obtained 16 species in general. The wealth estimator “Jack-knife1” indicated that the collections were sufficient. The group of medium and large mammals presented species with higher relative frequencies. Similarity indices showed greater similarity between brushwood area and Braquiaria in relation to total species richness, and the lowest similarity was found between Braquiaria and Cerrado. The results indicate that brushwood area seems to have formed the so-called ecological triggers, offering better conditions of shelter and protection for animals, causing an increase in species richness and, consequently, increasing the inter-specific interactions, resulting in greater similarity between this area and Cerrado. Due to the proximity between the areas and the permeability of brushwood area to fauna, Braquiaria can serve as a corridor for animals of more general behavior that transit from Cerrado to brushwood area, causing its enrichment and benefiting the degraded area. Future studies with new sampling areas without influence of nucleation technique and new methodologies of fauna sampling may help elucidate even more the issues raised here.